John Murtagh's patient education - Murtagh, John , 1936- (McGraw Hill Education, 2012)
John Murtagh's Patient Education is the essential aid for doctors in practice, general practice nurses, medical students, pharmacists and consumers needing accurate information in an age of internet selfishness. First published in 1992 and now in its sixth edition, it is the proven international standard for patient education material. -- Provided by publisher